Since both equations are already solved for y, we can set them equal to each other and solve for x.
-3x + 4 = -7x
To solve this equation, we can subtract -3x from both sides:
4 = -4x
Now, divide both sides by -4 to solve for x:
x = -1
Now that we know x = -1, we can substitute this value into either of the original equations to solve for y. Let's substitute it into the first equation:
y = -3(-1) + 4
y = 3 + 4
y = 7
Therefore, the solution is x = -1 and y = 7.
Solve the system by substitution.
y, equals, minus, 3, x, plus, 4
y=
−3x+4
y, equals, minus, 7, x
y=
−7x
1 answer